Network analysis of master regulators associated with invasive phenotypes in multiple myeloma - Qian, Feng; Wang, Yubo; Shi, Qinghong (Frontiers in Cell and Developmental Biology, 2025)
To elucidate the role of transcriptional regulators (TRs) associated with invasiveness in multiple myeloma (MM), we conducted a systematic network analysis to identify key master regulators (MRs) that govern MM invasiveness. We employed a consensus clustering method based on a 24-gene signature to classify MM patients into high invasiveness (INV-H) and low invasiveness (INV-L) groups. Subsequently, we identified TRs specific to the INV-H and INV-L phenotypes as MRs using a network-based approach, and we validated the MR activities that correlated with the INV-H phenotype across multiple independent datasets. We evaluated the effect of MRs on patient outcomes in relation to the prognosis of MM. By utilizing siRNA to disrupt ERG expression in U266 and RPMI8226 cell lines, we evaluated the effects of the master regulator ERG on the proliferation, apoptosis, invasion, and migration of myeloma cell lines, and we confirmed the expression of ERG in patients with extramedullary MM. We assessed invasiveness using a 24-gene signature, categorizing patients into INV-H and INV-L groups. Our network identified MRs linked to MM invasiveness and revealed enriched signaling pathways. High ERG expression correlated with poor prognosis. ERG silencing reduced cell invasiveness, migration, and apoptosis, while promoting proliferation. Elevated ERG was found in extramedullary MM, and potential drug candidates, including Idarubicin, were identified for treatment. This study provides a comprehensive analysis of master regulators in EMM, contributing to targeted therapeutic strategies. We identified ERG as a marker for extramedullary invasion in MM, suggesting it as a potential therapeutic target for future interventions.